Evaluation of probability distribution functions for fitting stem diameters of Tectona grandis plantation in Adekunle Ajasin University, Ondo State, Nigeria (Agriculture, Food, and Natural Resources Journal, 2025)
Modeling frequency distributions of tree variables, such as Diameter at Breast Height (DBH) plays an important role in forest inventories, growth prediction, and management. The objective of the study was to evaluate the 2- and 3-parameter Gamma, Log logistics, Log normal, and Weibull distribution functions fitted to the DBH of Teak (Tectona grandis Linn. F.) plantation in Adekunle Ajasin University, Akungba Akoko, Ondo State, Nigeria, for sustainable management. The method adopted for this research was complete enumeration of the teak plantation of size 80 m² x 40 m². The performance of the selected probability distribution functions (PDFs) was compared using Kolmogorov-Smirnov (K-S), Anderson-Darling (A-D), and Chi-square (ꭓ2) tests. The results showed that the highest frequency (526) of trees falls between the DBH of 0.11-0.14 m. The Weibull 3-parameter distribution had the best fit with K-S= 0.0222, A-D= 0.3908, and ꭓ2=10.868 and was followed by the Weibull 2-parameter distribution with K-S= 0.0238, A-D= 0.4944, and ꭓ2=10.443. Hence, Weibull 3 and 2-parameter were adjudged as the most suitable distributions, also based on the smallest relative rank sum of 17 and 27, respectively, in the study area. The study recommends the Weibull 3-parameter for DBH class distribution of the Tectona grandis plantation in the study area for plausible management and value projection.
Keywords: Diameter at Breast Height; Enumeration; Goodness of fit; Management; Model